A high-fibre personalised dietary advice given via a web tool reduces constipation complaints in adults. (28th April 2022) - Rijnaarts, Iris; de Roos, Nicole M.; Wang, Taojun; Zoetendal, Erwin G.; Top, Jan; Timmer, Marielle; Hogenelst, Koen; Bouwman, Emily P.; Witteman, Ben; de Wit, Nicole
Abstract: Constipation can greatly impact the quality of life (QoL), which can be relieved by dietary fibres; however, preserving a higher fibre intake remains a challenge. We investigated the effects of a personalised dietary advice (PDA) on fibre intake and mild constipation complaints. A total number of twenty-five adults with mild constipation complaints were included in a 4-week observation period followed by a 4-week personalised intervention. The PDA provided high-fibre alternatives via a web tool. In weeks 1, 4 and 8, dietary intake, constipation complaints and QoL were assessed. Furthermore, participants collected a faecal sample at weeks 1, 4 and 8 to determine microbiota diversity and composition, and short-chain fatty acids (SCFA). Participants completed questions daily for 8 weeks regarding abdominal complaints, stool frequency and stool consistency. Fibre intake in week 8 was significantly higher compared to week 1 ( Δ = 5·7 ± 6·7 g, P < 0·001) and week 4 ( Δ = 5·2 ± 6·4 g, P < 0·001). Constipation severity and QoL significantly improved at week 8 compared to the observation period ( P < 0·001). A higher fibre intake significantly reduced constipation severity ( β = −0·031 (−0·05; −0·01), P = 0·001) and the QoL ( β = −0·022 (−0·04; −0·01), P = 0·009). Stool consistency ( P = 0·040) and abdominal pain ( P = 0·030) improved significantly during the intervention period ( P = 0·040), but stool frequency did not. Average microbial alpha diversity and composition and SCFA concentrations did not change over time, but indicated individual-specific dynamics. Several SCFAs were associated with constipation complaints. To conclude, a PDA effectively increased fibre intake and subsequently reduced constipation complaints, indicating that guided dietary adjustments are important and feasible in the treatment of mild constipation complaints.